1997
DOI: 10.1007/s004200050178
|View full text |Cite
|
Sign up to set email alerts
|

The risk of occupational rhinitis

Abstract: Furriers, bakers, and livestock breeders had the most elevated relative risk of occupational rhinitis. Occupational rhinitis cases reported at a younger age than asthma, suggesting that rhinitis often precedes asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
1
3

Year Published

1997
1997
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(34 citation statements)
references
References 15 publications
3
27
1
3
Order By: Relevance
“…This matrix is currently used in analyses of the ECRHS and was used in a recently published work by RADON et al [20]. Causative agents of rhinitis and asthma are very similar [21] and it was repeatedly reported than rhinitis often precedes the development of asthma symptoms in allergic patients [22]. Therefore, the current authors believe the JEM to be an acceptable instrument to evaluate risk exposure for rhinitis.…”
Section: Discussionmentioning
confidence: 97%
“…This matrix is currently used in analyses of the ECRHS and was used in a recently published work by RADON et al [20]. Causative agents of rhinitis and asthma are very similar [21] and it was repeatedly reported than rhinitis often precedes the development of asthma symptoms in allergic patients [22]. Therefore, the current authors believe the JEM to be an acceptable instrument to evaluate risk exposure for rhinitis.…”
Section: Discussionmentioning
confidence: 97%
“…; 135), mites (136), latex (137), enzymes (138), grains (bakers and agricultural workers; 139,140) and chemicals such as acid anhydrides, platinum salts (141), glues and solvents (142). Occupational rhinitis is frequently underdiagnosed due to under-reporting and/or a lack of doctor awareness (133,143). Diagnosis is suspected when symptoms occur in relation to work.…”
Section: Work-related Rhinitis Occupational Rhinitis Arises In Respomentioning
confidence: 99%
“…Children with allergic rhinitis have been reported to be seven times more likely to have asthma and wheezing illness than children without rhinitis symptoms [19]. A recent study has also shown that the highest incidence of occupational rhinitis occurs in younger age groups than the highest incidence of asthma, supporting the contention that rhinitis often precedes asthma [20].…”
Section: Discussionmentioning
confidence: 93%